Clinical Effectiveness of Ashwagandha in Menopause: A Systematic Review - Frederick Wirawan; Putu Enrico Pramana Okaniawan; Isharyah Sunarno (Bali Medical and Wellness Journal, 2026)
Background: Menopause is the natural and permanent cessation of menses, often accompanied by vasomotor symptoms that can impact a person's quality of life. Ashwagandha (Withania somnifera), also known as Indian ginseng, has been shown to ameliorate some of the symptoms associated with menopause in women, particularly climacteric symptoms. Objective: This study aimed to evaluate Ashwagandha (Withania somnifera) in reducing menopausal symptoms and improving quality of life, as measured by the Menopause Rating Scale (MRS) and the Menopause-Specific Quality of Life (MENQOL) questionnaire. Methods: A systematic review was conducted following the PRISMA guidelines, with pre-defined keywords and pre-determined inclusion and exclusion criteria. Risk of bias was assessed using RoB 2 for RCTs and ROBINS-I for non-RCTs. Results: Based on the inclusion criteria, 7 studies were identified: 4 randomized controlled trials (RCTs) and 3 non-randomized trials. The RCTs were judged to have low risk of bias, while the non-randomized trials were judged to have high (serious) risk of bias. Menopausal symptom outcomes were measured using MRS (2 studies), MENQOL (2 studies), both MRS and MENQOL (2 studies), and MENQOL with SGA (1 study). Six of the 7 studies showed significant improvement in menopausal symptoms and quality of life with the use of Ashwagandha (Withania somnifera), while the remaining study observed a tendency toward improvement but lacked a control group. Conclusion: Ashwagandha (Withania somnifera) shows potential in alleviating menopausal symptoms and improving quality of life. These findings suggest that Ashwagandha may serve as a promising non-hormonal option to support integrative healthcare for women during the menopausal stage.